Case Report: Inferior Vena Cava Agenesia in a Young Male Patient Presenting With Bilateral Iliac Veins Thrombosis - Pasqui, Edoardo; de Donato, Gianmarco; Camarri, Silvia; Molinari, Raffaele; Cascinelli, Irene; Pelini, Veronica; Abate, Luigi; Palasciano, Giancarlo (Frontiers in Surgery, 2022)
Introduction Anomalies in inferior vena cava represent an uncommon finding with a prevalence of 0. 3 to 0.5% among healthy patients. Specifically, the condition characterized by the agenesis of the inferior vena cava (IVC; AIVC) has been observed among the 0.0005 to 1% of the general population. AIVC is strongly related to deep vein thrombosis (DVT) of the lower limb and pelvic district, especially in young patients. The rarity of the presented condition could relate to an underestimation of its impact on a particular clinical setting leading to a delayed diagnosis and inaccurate early- and long-term management. Report We presented a case of this anomaly regarding a 31-year-old man presenting with bilateral symptomatic proximal DVT. Duplex vascular ultrasound and subsequent CT-angiography revealed the complete occlusion of the right external and common iliac vein, as well as partial occlusion of the contralateral external iliac vein, in the patient. The exam also revealed the interruption of IVC in its infrarenal part. At the level of renal veins coalescence, IVC appeared again in its usual position. A dilatated portal system, hepatic veins, and azygos and hemiazygos systems were also highlighted. Anticoagulation was promptly started with the administration of Fondaparinux (7.5 mg/die). In addition, compression stocking was initiated within 24 h from diagnosis. After 3 weeks, the anticoagulation regimen was shifted toward the administration of a direct oral anticoagulant (Apixaban; 5 mg two times a day). At 1-month follow-up, a vascular duplex ultrasound revealed a complete resolution of the iliac veins' thrombosis. Conclusion It is important to consider the eventuality of IVC anomalies in a young adult presenting with unexplained, extensive, or bilateral DVT. Accurate diagnostic evaluation is necessary to fully identify this condition that could represent a real challenge.